2020
DOI: 10.1111/isj.12274
|View full text |Cite
|
Sign up to set email alerts
|

Usable, in‐use, and useful research: A 3U framework for demonstrating practice impact

Abstract: In addition to innate curiosity, many of us also see scientific research as a way of making the world a better place. There has been a drive to better understand and observe the practical and societal impact of research, led by researchers seeking to find meaning and purpose in their work, as well as government agencies responsible for allocating research funding to maximum effect. Despite a wealth of guidance from researchers discussing impact and agencies evaluating impact, making practice impact visible and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…The utilization of research is also expected to have observable benefits on outcomes that matter in practice. The most recent framework by Pan and Pee ( 2020 ) covers all the common types of impact while distinguishing between efficiency and effectiveness as valuable outcomes of research utilization (see Table 2 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The utilization of research is also expected to have observable benefits on outcomes that matter in practice. The most recent framework by Pan and Pee ( 2020 ) covers all the common types of impact while distinguishing between efficiency and effectiveness as valuable outcomes of research utilization (see Table 2 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The most recent framework by Pan and Pee ( 2020 ) covers all the common types of impact while distinguishing between efficiency and effectiveness as valuable outcomes of research utilization (see Table 2 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many new opportunities, such as citizen science (Levy & Germonprez, 2017;Lukyanenko et al, 2019) and other forms of engaged research, that are found rather rarely in IS research. Journal editors and conference organisers could equally promote the prevalence of such research by, for example, establishing new genres and formats, such as policy briefs and software reviews (Pan & Pee, 2020), that facilitate expanding the societal impact of IS research. This would particularly help more problem-driven and engaged scholars to obtain recognition for their work under the current citation-based promotion and tenure system.…”
Section: Recommendations For Moving Forward and Making A Differencementioning
confidence: 99%
“…In the sixth article, Pan and Pee () note that research should make the world a better place. They consider the practice impact of research by addressing three questions that frequently arise among researchers: What constitutes practice impact?…”
mentioning
confidence: 99%